The Commercial Paper Funding Facility - Nina Boyarchenko; Richard K. Crump; Anna Kovner; Deborah Leonard (Federal Reserve Bank of New York, 2021)
The Federal Reserve reestablished the Commercial Paper Funding Facility (CPFF 2020) in response to the disruptions in the commercial paper market triggered by the COVID-19 pandemic and subsequent economic shutdowns. The CPFF 2020 was designed to support market functioning and provide a liquidity backstop for the commercial paper market. This paper provides an overview of the CPFF 2020, including detailing the facility's design, documenting its usage, and describing its impact on commercial paper markets. In addition, we compare the market conditions and facility design in CPFF 2020 to that of the original CPFF facility.
Keywords: G12; G18; G19; 330; Federal Reserve; commercial paper market; CPFF; Federal Reserve lending facilities